Botanical drugs and their natural compounds: a neglected treasury for inhibiting the carcinogenesis of pancreatic ductal adenocarcinoma - Yunfei Dai; Xi Guan; Fangyue Guo; Xin Kong; Shuqi Ji; Dong Shang; Changchuan Bai; Qingkai Zhang; Liang Zhao (Pharmaceutical Biology)
Context Pancreatic ductal adenocarcinoma (PDAC), which is characterized by its malignant nature, presents challenges for early detection and is associated with a poor prognosis. Any strategy that can interfere with the beginning or earlier stage of PDAC greatly delays disease progression. In response to this intractable problem, the exploration of new drugs is critical to reduce the incidence of PDAC.Objective In this study, we summarize the mechanisms of pancreatitis-induced PDAC and traditional Chinese medicine (TCM) theory and review the roles and mechanisms of botanical drugs and their natural compounds that can inhibit the process of pancreatitis-induced PDAC.Methods With the keywords ‘chronic pancreatitis’, ‘TCM’, ‘Chinese medicinal formulae’, ‘natural compounds’, ‘PDAC’ and ‘pancreatic cancer’, we conducted an extensive literature search of the PubMed, Web of Science, and other databases to identify studies that effectively prevent PDAC in complex inflammatory microenvironments.Results We summarized the mechanism of pancreatitis-induced PDAC. Persistent inflammatory microenvironments cause multiple changes in the pancreas itself, including tissue damage, abnormal cell differentiation, and even gene mutation. According to TCM, pancreatitis-induced PDAC is the process of ‘dampness-heat obstructing the spleen and deficiency due to stagnation’ induced by a variety of pathological factors. A variety of botanical drugs and their natural compounds, such as Chaihu classical formulae, flavonoids, phenolics, terpenoids, etc., may be potential drugs to interfere with the development of PDAC via reshaping the inflammatory microenvironment by improving tissue injury and pancreatic fibrosis.Conclusions Botanical drugs and their natural compounds show great potential for preventing PDAC in complex inflammatory microenvironments.